2001
DOI: 10.1186/rr43
|View full text |Cite
|
Sign up to set email alerts
|

Role of epidermal growth factor receptor activation in regulating mucin synthesis

Abstract: commentary review reports primary research COPD = chronic obstructive pulmonary disease; EGF(R) = epidermal growth factor (receptor); MAPK = mitogen-activated protein kinase; TGF = transforming growth factor; TNF = tumor necrosis factor. Available online http://respiratory-research.com/content/2/2/085 IntroductionEpidermal growth factor (EGF) was discovered by Cohen, and he and his colleagues subsequently extended our knowledge of the mechanisms of action of EGF and its receptor EGFR [1]. EGFR is a 170 kDa mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Moreover, pharmacological inhibition with specific tyrosine kinase inhibitors suggested that tyrosine phosphorylation events downstream of EGFR engagement were necessary for TGF-␣-induced mucin up-regulation. These studies also suggested that TNF-␣ triggered this response presumably by upregulating the expression of EGFR (19,26). However, in vivo evidence of this proposed pathway is not firmly established, and the actual signal transduction pathway presumably engaged by tyrosine phosphorylation and leading to mucus production remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pharmacological inhibition with specific tyrosine kinase inhibitors suggested that tyrosine phosphorylation events downstream of EGFR engagement were necessary for TGF-␣-induced mucin up-regulation. These studies also suggested that TNF-␣ triggered this response presumably by upregulating the expression of EGFR (19,26). However, in vivo evidence of this proposed pathway is not firmly established, and the actual signal transduction pathway presumably engaged by tyrosine phosphorylation and leading to mucus production remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR has been strongly implicated in the pathogenesis of Th2 tissue inflammation via its ability to regulate goblet cell metaplasia, mucin synthesis, and epithelial cell proliferation, differentiation, and survival (12,(27)(28)(29). Recent studies demonstrated that EGFR signaling mediates allergen-induced chemokine (TARC/CCL17) release by lung epithelial cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Mucin hypersecretion is commonly observed in many respiratory diseases, such as rhinitis, sinusitis, otitis media, nasal allergy, chronic bronchitis, and cystic fibrosis (1)(2)(3)(4). Eighteen types of mucin genes have been discovered to date: MUC1 (5), MUC2 (6), MUC3 (7), MUC4 (8), MUC5AC (9), MUC5B (10), MUC6 (11), MUC7 (12), MUC8 (13), MUC9 (14), MUC10 (15), MUC11 (16), MUC12 (16), MUC13 (17), MUC15 (18), MUC16 (19), MUC17 (20), and MUC18 (21).…”
mentioning
confidence: 99%